2014
DOI: 10.2147/ijn.s71310
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dots immunofluorescence histochemical detection of EGFR gene mutations in the non-small cell lung cancers using mutation-specific antibodies

Abstract: Background Epidermal growth factor receptor (EGFR) mutation status plays an important role in therapeutic decision making for non-small cell lung cancer (NSCLC) patients. Since EGFR mutation-specific antibodies (E746-A750del and L858R) have been developed, EGFR mutation detection by immunohistochemistry (IHC) is a suitable screening test. On this basis, we want to establish a new screening test, quantum dots immunofluorescence histochemistry (QDs-IHC), to assess EGFR gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Su et al reported iodine doped carbon dots conjugated with cetuximab as a dual fluorescent/CT probe for bioimaging lung cancer cells epidermal growth factor receptor (EGFR) (16). Additionally, QDs immunofluorescence histochemistry (QDs-IHC) was employed to detect EGFR mutant, RRM2 and Bcl2, and Monocarboxylate transporter 4 (MCT-4) in non-small cell lung cancer patients (17).…”
Section: Bioapplications Of Qds In Lung Pulmonary System Related Bioimagingmentioning
confidence: 99%
“…Su et al reported iodine doped carbon dots conjugated with cetuximab as a dual fluorescent/CT probe for bioimaging lung cancer cells epidermal growth factor receptor (EGFR) (16). Additionally, QDs immunofluorescence histochemistry (QDs-IHC) was employed to detect EGFR mutant, RRM2 and Bcl2, and Monocarboxylate transporter 4 (MCT-4) in non-small cell lung cancer patients (17).…”
Section: Bioapplications Of Qds In Lung Pulmonary System Related Bioimagingmentioning
confidence: 99%
“…During in-vivo studies, QDs coated with PEG were not recognized by the reticuloendothelial system increasing their circulation time within the biological system [123]. QDs are also used for biological imaging, cellular and molecular tracing, estimating toxicity profile, in-vitro imaging (multiplexed), molecular labelling as markers, signal transduction and immuno-histochemical detection [124]. The aqueous solubility of QDs can be increased by coating them with polymer and ligand exchange [71] [125].…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Furthermore, designing probes to detect disease specific mutations is an attractive approach toward early clinical identification of the different cancers. QDs linked to EGFR mutation-specific antibodies were assessed and reported to be highly effective and sensitive as compared with traditional methods in disease diagnosis and therapeutic decision making for NSCLC patients (Qu et al, 2014). In an attempt to further improve the diagnostic ability of these molecules, a highly specific QDs based recognition-before-labeling strategy using DNA aptamers was developed.…”
Section: Qds For Lung Cancer Diagnosis and Therapeuticsmentioning
confidence: 99%